Process standardization, characterization and shelf life studies of Chhana jalebi - A traditional Indian milk sweet - Geetha, P. (2016)
Chhana jalebi is a popular product in middle and northern parts of India and is prepared by frying of batter made from chhana, maida and water and finally soaking in sugar syrup. This chhana based fried sweet product is being prepared and sold by halwais in Indian sweet market. It has a coiled structure with syrupy interiors and chewy body. It has close resemblance to maida jalebi and khoa jalebi, but has firmer coils. The manufacturing procedure varies widely from manufacturer to manufacturer. There was no proper (standard) manufacturing method available for the preparation of chhana jalebi. Hence, a study was conducted to standardize a method for its manufacture consequently it will be helpful to produce the jalebi on a commercial scale. The chhana jalebi was standardized by various process parameters such as fat level in milk 3%, ratio of maida - chhana combination 1:1, water level in batter 45%, frying time and temperature 160-170°C, sugar syrup concentration 68°Brix and soaking time 2 min. Standardized product was analyzed by various physical, chemical, microbial, sensory and textural characteristics. The product had a light brown coloured coiled appearance, crispy body and texture. The nutritional composition percentage of chhana jalebi was protein 5.71±0.20, carbohydrate 67.11±0.19, fat 12.53±0.17 and moisture 20.23±0.25. The shelf life of the jalebi was found to be 5 days at 28°C. This was enhanced to 18 days by using potassium sorbate as preservative at the permitted levels. The optimized process and enhanced shelf life will pave way for commercialization and mechanization of chhana jalebi by food industry.